2009
DOI: 10.1111/j.1526-100x.2010.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Seedling Establishment Rates in Zostera marina and Their Implications for Seagrass Restoration

Abstract: Selection of strategies to efficiently utilize limited seed supplies in efforts to restore the seagrass Zostera marina (eelgrass) requires a better understanding of the processes that limit seedling establishment at potential restoration sites. We investigated the effect of seed distribution timing on seedling establishment and tested for interactive effects of seed burial and distribution timing. We also investigated the effect of habitat type on seedling establishment by distributing Z. marina seeds inside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
0
26
1
Order By: Relevance
“…The use of seedlings for this purpose (Lewis 1987, Balestri et al 1998, Kirkman 1999 and to evaluate different planting techniques (Marion andOrth 2010 , Zarranz et al 2010 ) has been satisfactory. In the case of P. oceanica , the only previous attempts to use seedlings in restoration were those of Balestri et al (1998) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of seedlings for this purpose (Lewis 1987, Balestri et al 1998, Kirkman 1999 and to evaluate different planting techniques (Marion andOrth 2010 , Zarranz et al 2010 ) has been satisfactory. In the case of P. oceanica , the only previous attempts to use seedlings in restoration were those of Balestri et al (1998) .…”
Section: Discussionmentioning
confidence: 99%
“…Seagrass canopies decrease wave energy reaching the sediment−water interface, and consequently reduce sediment resuspension (Koch et al 2006, Hansen & Reidenbach 2012. Higher initial success of seedlings might therefore be expected within established canopies, although experiments in Ruppia maritima canopies found no enhancement for surface seeds (Marion & Orth 2010b), and seedlings establishing within Z. marina canopies subsequently face light competition from adult plants (Olesen 1999). We suggest that Z. marina is more likely than R. maritima to reduce wave and current energy within the meadow, enhancing seedling establishment within sand gaps and creating a positive feedback cycle for meadow persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary trials during the development of this technique showed reliable planting in the target 2 to 3 cm depth range. All seeds used were individually assessed as viable seeds exhibiting an intact seed coat, high density, and rapid fall velocity in seawater (Marion & Orth 2010b). Plots were placed in 2 rows along a 210 m × 10 m constant-depth region parallel to the shoreline at each site, and were divided into 4 blocks for sampling.…”
Section: Germination Failure For Surface and Buried Seedsmentioning
confidence: 99%
“…Seeded plots were separated by at least 60 to 100 m of unvegetated bottom, though patterns varied among bays and years. Additional small-scale seed experi- ments covering 1 to 4 m 2 were conducted in all 4 bays between 1999 and 2008, but these represented <1% of the total seeds broadcast over the 11 yr time period (Orth et al 2003, Marion & Orth 2010b. Plot sizes, numbers, and seeding densities used each year were generally determined by seed availability and the design of individual experiments conducted as part of the restoration effort (e.g.…”
Section: Seed Collection and Distributionmentioning
confidence: 99%
“…For large plots (>100 m 2 ), seedlings were counted in 1 m line transects along the diagonals of each plot, and initial seedling establishment rates were calculated. Seedling establishment was assessed in smaller-scale experimental plots by complete counts of seedlings (Orth et al 2003, Marion & Orth 2010b. Data from both scales was used to assess seedling success for each bay.…”
Section: Seed Collection and Distributionmentioning
confidence: 99%